Functional capacity and family dysfunction of the elderly in the family health strategy program in Ceará, Brazil: a cross-sectional study - Andrade Silva, Alyne; de Oliveira Ferreira, Glauciano; Ferreira Felício, Janiel; Valúzia Guedes Guerra, Francisca; Chaves Costa, Edmara; Pessoa Moreira, Rafaella (O Mundo da Saúde, 2020)
Factors related to aging may interfere with functional capacity and family dysfunction among the elderly population. This has implications for the care provided and directs care planning to the most dependent elderly. Thus, the objective of this study was to analyze the functional capacity and family dysfunction of elderly people assisted in the Family Health Strategy in Fortaleza, Ceará. A quantitative, cross-sectional, descriptive study was carried out with 99 elderly people from a Primary Health Care Unit in Fortaleza, CE. Data collection took place between December 2015 and February 2016. The functional capacity and family relationships of the elderly were evaluated using the scales of Basic Activities of Daily Living and Instrumental Activities of Daily Living scales, as well as the APGAR Family Index. Descriptive statistics, chi-squared tests and Fisher’s exact tests were used. It was observed that 82 (82.8%) of the elderly demonstrated independence for all basic activities of daily living and 59 (59.6%) were classified as independent in the assessment of instrumental activities of daily living. The application of the APGAR Family Index showed that 67 (67.6%) of the participants had a perception of good family functionality. Thus, assessing family functionality showed that most elderly people had families considered to be functional, which is a positive factor for their well-being.